2019
DOI: 10.5267/j.msl.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The economic and energy efficiencies of GCC states: A DEA approach

Abstract: The six GCC states share similar economic, geographic and socio-cultural characteristics and also face with similar challenges in terms of energy perspective. This study plans to focus on the economic and energy efficiency of the six GCC states. In the process, the study ranks the GCC states in terms of their efficiency scores. These efficiencies are computed through Data Envelopment Analysis. The economic efficiency is calculated for all six GCC states. Capital and labor are the inputs and GDP is the output. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In order to promote agricultural development in China's central and western regions, we need to take into account the differences in resources, environment, human resources, and other conditions across different regions, despite the economic development in the eastern region. (3) Our analysis of the DSBM difference variables reveals that the factors affecting agricultural production efficiency vary across the different regions of China, and appropriate resource allocation needs to occur based on the needs of each region [15,16]. For instance, the eastern region requires the most adjustment in terms of rural electricity consumption, with the Hebei and Liaoning administrative regions needing the most adjustment.…”
Section: China's Agricultural Production Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to promote agricultural development in China's central and western regions, we need to take into account the differences in resources, environment, human resources, and other conditions across different regions, despite the economic development in the eastern region. (3) Our analysis of the DSBM difference variables reveals that the factors affecting agricultural production efficiency vary across the different regions of China, and appropriate resource allocation needs to occur based on the needs of each region [15,16]. For instance, the eastern region requires the most adjustment in terms of rural electricity consumption, with the Hebei and Liaoning administrative regions needing the most adjustment.…”
Section: China's Agricultural Production Efficiencymentioning
confidence: 99%
“…To gather the literature related to agricultural production efficiency, productivity changes, and other relevant studies, the following steps were taken: Previous studies have found that important factors affecting agricultural productivity in Asian countries include scientific and technological progress [1][2][3][4][5], taxation [6], and capital investment [7]. The main factors affecting agricultural efficiency include machinery and fertilizer inputs [6,[8][9][10][11][12], energy use [8][9][10][11][12][13][14][15][16], irrigation infrastructure [16,17], agricultural machinery [18], and pesticides [19]. The main factors related to agriculture and the environment include the burning of crops [20,21], greenhouse gas emissions [22], national agricultural policies [23], and differences between greenhouse and open field cultivation [24].…”
Section: Introductionmentioning
confidence: 99%